2023
DOI: 10.1002/uog.26072
|View full text |Cite
|
Sign up to set email alerts
|

Fetal left‐atrial posterior‐space‐to‐diagonal ratio at 17–37 weeks' gestation for prediction of total anomalous pulmonary venous connection

Abstract: The left-atrial posterior-space-to-diagonal (LAPSD) ratio and post-left atrium space (PLAS) index are significantly higher in cases of total anomalous pulmonary venous connection (TAPVC) than in fetuses with a normal heart, independent of whether fetal TAPVC is isolated or associated with complex additional cardiac lesions. In normal fetuses, the LAPSD ratio and PLAS index demonstrate a minimal decrease during gestation and can be considered age-independent parameters. Both indices are independent of fetal gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…[ 13 ] Other studies have confirmed its reliability in differentiating TAPVR from normal cases, showing low inter- and intraobserver variabilities. [ 10 12 ] Notably, the post-LA space index was independent of the gestational age,[ 13 ] the four-chamber view orientation (apical, basal, or lateral), and the TAPVR type. [ 12 ] Studies have demonstrated that post-LA space index cutoff value of ≥1.27 or 1 exhibited excellent diagnostic performance with a sensitivity of 100% and specificity of 99% and 95.1%, respectively.…”
Section: Ndirect S Onographic M ...mentioning
confidence: 99%
See 3 more Smart Citations
“…[ 13 ] Other studies have confirmed its reliability in differentiating TAPVR from normal cases, showing low inter- and intraobserver variabilities. [ 10 12 ] Notably, the post-LA space index was independent of the gestational age,[ 13 ] the four-chamber view orientation (apical, basal, or lateral), and the TAPVR type. [ 12 ] Studies have demonstrated that post-LA space index cutoff value of ≥1.27 or 1 exhibited excellent diagnostic performance with a sensitivity of 100% and specificity of 99% and 95.1%, respectively.…”
Section: Ndirect S Onographic M ...mentioning
confidence: 99%
“…[ 12 ] Studies have demonstrated that post-LA space index cutoff value of ≥1.27 or 1 exhibited excellent diagnostic performance with a sensitivity of 100% and specificity of 99% and 95.1%, respectively. [ 10 12 ]…”
Section: Ndirect S Onographic M ...mentioning
confidence: 99%
See 2 more Smart Citations
“…Today, in experienced hands, most major CHDs can be detected in the second trimester 3 and approximately two-thirds of major CHDs can be diagnosed before 14 weeks of gestation 4,5 . Yet, even in an era in which exome sequencing is feasible 6 , CHD diagnosis remains suboptimal, owing in large part to the complexity of cardiac anatomy and function, and the inherent difficulty of ultrasound examination of the fetal heart 7,8 . Accordingly, in countries in which a national screening program for CHD exists, on average only 50% of major CHD is recognized during pregnancy 9 .…”
mentioning
confidence: 99%